Change in the neurochemical signature and morphological development of the parvocellular isthmic projection to the avian tectum. Issue 2 (17th August 2021) - Reyes‐Pinto, Rosana; Ferrán, José L.; Vega‐Zuniga, Tomas; González‐Cabrera, Cristian; Luksch, Harald; Mpodozis, Jorge; Puelles, Luis; Marín, Gonzalo J.
Abstract: Neurons can change their classical neurotransmitters during ontogeny, sometimes going through stages of dual release. Here, we explored the development of the neurotransmitter identity of neurons of the avian nucleus isthmi parvocellularis (Ipc), whose axon terminals are retinotopically arranged in the optic tectum (TeO) and exert a focal gating effect upon the ascending transmission of retinal inputs. Although cholinergic and glutamatergic markers are both found in Ipc neurons and terminals of adult pigeons and chicks, the mRNA expression of the vesicular acetylcholine transporter, VAChT, is weak or absent. To explore how the Ipc neurotransmitter identity is established during ontogeny, we analyzed the expression of mRNAs coding for cholinergic (ChAT, VAChT, and CHT) and glutamatergic (VGluT2 and VGluT3) markers in chick embryos at different developmental stages. We found that between E12 and E18, Ipc neurons expressed all cholinergic mRNAs and also VGluT2 mRNA; however, from E16 through posthatch stages, VAChT mRNA expression was specifically diminished. Our ex vivo deposits of tracer crystals and intracellular filling experiments revealed that Ipc axons exhibit a mature paintbrush morphology late in development, experiencing marked morphological transformations during the period of presumptive dual vesicular transmitter release. Additionally, although ChAT protein immunoassays increasingly label the growing Ipc axon, this labeling was consistently restricted to sparse portions of the terminal branches. Combined, these results suggest that the synthesis of glutamate and acetylcholine, and their vesicular release, is complexly linked to the developmental processes of branching, growing and remodeling of these unique axons. Abstract : The "paintbrush" axon terminals from neurons of the nucleus isthmi parvocellularis (Ipc) exert a powerful boosting effect upon the ascending visual transmission in the optic tectum of birds. Although classically considered a cholinergic nucleus, Ipc neurons in adult chicks express VGLUT2 instead of VAChT. Performing in situ hybridization and immunohistochemistry in chick embryos, the authors find that both vesicular transporters are strongly expressed in Ipc neurons throughout development, along with other cholinergic markers, but there is a marked decrease in VAChT expression before hatching. Ex vivo deposits of tracer crystals and intracellular fillings reveal that Ipc axons exhibit conspicuous morphological transformations until late in development, suggesting that the presumptive dual vesicular transmitter release might be related to the growing and remodeling of this complex axon.